Mitigating Lecturers’ Communication Uncertainty in Using SWVC During Online Lectures - Palupi, Palupi; Primandaru, Danendra Aflihandito (ETTISAL : Journal of Communication, 2024)
This study investigates at the communication uncertainty undergraduate lecturers face when delivering lectures through synchronous web video conferencing (SWVC) during online lectures. Uncertainty Reduction Theory (URT) is employed to understand how lecturers use communication techniques to reduce uncertainty in online lecture. Undergraduate lecturers at Universitas Muhammadiyah Surakarta who have ever conducted teaching online were interviewed in semi-structured interviews. Thematic analysis is performed, with a particular focus on the methods that lecturers use to communicate with their students in order to build relationships and reduce uncertainty. The study identifies a number of important areas of uncertainty, such as technical challenges, the development of useful learning materials, evaluation of comprehension, student involvement, and conduct during online sessions. This study shows how lecturers use active, passive, and interactive strategy to reduce uncertainty. These results underline how crucial it is to deal with technology challenges, advance interactive teaching strategies, raise student participation, and establish effective communication in order to guarantee successful online education in the face of uncertainty.